Ginkgo biloba Leaf Extract Protects against Myocardial Injury via Attenuation of Endoplasmic Reticulum Stress in Streptozotocin-Induced Diabetic ApoE−/− Mice. (25th February 2018) - Tian, Jinfan; Liu, Yanfei; Liu, Yue; Chen, Keji; Lyu, Shuzheng
Abstract : Diabetes was induced in high-fat diet-fed ApoE −/− mice via administration of low-dose streptozotocin (STZ) for five days. Mice were then treated with GBE (200 or 400 mg/kg) by gastric gavage daily for 12 weeks. Mice in the untreated diabetic group received saline instead, and nondiabetic C57BL/6J mice served as controls. Collagen І and ІІІ mRNA expression was measured by real-time PCR. TNF- α, IL-1 β mRNA levels, and NF- κ B expression were determined to analyze intramyocardial inflammation. Hallmarks of endoplasmic reticulum stress- (ERS-) related apoptosis pathways, including phosphorylated c-Jun N-terminal kinase (p-JNK), C/EBP homologous protein (CHOP), caspase-12, and cleaved caspase-3, were analyzed by Western blotting. Diabetic ApoE −/− myocardial injury was associated with increased cardiomyocyte apoptosis (increased expression of p-JNK, CHOP, caspase-12, and cleaved caspase-3), interstitial fibrosis (increased mRNA levels of collagen І and ІІІ), and inflammation (increased mRNA levels of TNF- α and IL-1 β, and NF- κ B expression). GBE at 200 and 400 mg/kg/day significantly attenuated cardiomyocyte apoptosis, collagen deposition, and inflammation in diabetic mice via inhibition of the p-JNK, CHOP, and caspase-12 pathways. Serum levels of the proinflammatory cytokines (IL-6, IL-1 β, and TNF- α ), blood glucose, and lipid profiles were also regulated by GBE treatment. GBE might be beneficial in the treatment of diabetic myocardial injury.